Making Room for Children: A Response to Professor Estin on Immigration and Child Welfare - Rick Su (Washington University Global Studies Law Review, 2018)
If children are increasingly the focus of immigration, then perhaps it is time that immigration focus on children. As Professor Estin reminds us, America has long been committed to the welfare and protection of children. This commitment is woven throughout American law. We affirm it as signatories to international accords. And when it comes to immigration, Congress has recognized the special challenges and vulnerabilities that children face—not only in getting to our country, but also in the immigration proceedings that follows. Nowhere is this more evident than the special protections and procedures in place for unaccompanied children in our immigration system. But despite all this, Professor Estin is also right that “[w]e could and should do better.” My fear is that things may get a lot worse before they get better. Not only are protections for children in our immigration system limited, but the protections that exist seem increasingly at risk. The prospects for federal partnerships with state and local child welfare agencies and courts, which have more experience and expertise with child welfare issues, seem increasingly remote as federal-local clashes escalate over immigration enforcement. All the while, the federal agencies that Congress has tasked with looking after the best interest of children struggle to handle their growing numbers and political pressures to prioritize enforcement above all else. Many of these problems are connected to President Trump and the policies and priorities of his administration. But I also want to suggest that the challenges go a lot deeper, and may be inherent in how the issue of immigration have traditionally been cast and the institutional manner in which it has historically been regulated. Overcoming these challenges, in my view, will require more than political will and zealous advocacy. It might also require us to rethink how our nation regulates immigration more generally.
Keywords: Child migrants; Child welfare; best interest; child immigrant; immigration